Students’ Perceptions on The Use of Tinkerbell Video in Listening Comprehension - Iswanto, Joko (Institut Teknologi Pendidikan Indonesia, 2025)
The study aimed to analyze students' perceptions on the use of Tinkerbell videos in listening comprehension. The objective of this research was to investigate students’ perceptions in using Tinkerbell video for listening comprehension at the 11th grade of SMKN 4 Tanjungpinang. This research was an analytical study using the purposive sampling method, which was 15 students as participants. This research used descriptive quantitative research design, utilizing questionnaire and interviews as the instruments. However, only seven students were interviewed. The researcher found that in cognitive sub-aspect of the questionnaire, 59% of the students agreed that Tinkerbell helps them learn many new words through listening. In the affective sub-aspect, 73% of students believed that watching Tinkerbell made them feel more comfortable studying English. In the conative sub-aspect, 67% of 15 students agreed that they should regularly record all new words from Tinkerbell in their books. However, in another conative sub-aspect, 73% of students disagreed, stating that Tinkerbell video had no impact on their ability to learn listening skills. Nevertheless, all interviewed students responded positively to using Tinkerbell videos to language learning, describing them as engaging, fun, and exciting.